Determining the Upper and Lower Limits of Cerebral Autoregulation With Cerebral Oximetry Autoregulation Curves: A Case Series. Issue 5 (May 2018) - Rivera-Lara, Lucia; Zorrilla-Vaca, Andres; Healy, Ryan J.; Ziai, Wendy; Hogue, Charles; Geocadin, Romergryko; Radzik, Batya; Palmisano, Caitlin; Mirski, Marek A.
Abstract : Objective: Critical care guidelines recommend a single target value for mean arterial blood pressure in critically ill patients. However, growing evidence regarding cerebral autoregulation challenges this concept and supports individualizing mean arterial blood pressure targets to prevent brain and kidney hypo- or hyperperfusion. Regional cerebral oxygen saturation derived from near-infrared spectroscopy is an acceptable surrogate for cerebral blood flow and has been validated to measure cerebral autoregulation. This study suggests a novel mechanism to construct autoregulation curves based on near-infrared spectroscopy–measured cerebral oximetry. Design: Case-series study. Setting: Neurocritical care unit in a tertiary medical center. Patients: Patients with acute neurologic injury and Glasgow coma scale score less than or equal to 8. Measurements and Main Results: Autoregulation curves were plotted using the fractional-polynomial model in Stata after multimodal continuous monitoring of regional cerebral oxygen saturation and mean arterial blood pressure. Individualized autoregulation curves of seven patients exhibited varying upper and lower limits of autoregulation and provided useful clinical information on the autoregulation trend (curves moving to the right or left during the acute coma period). The median lower and upper limits of autoregulation were 86.5 mm Hg (interquartile range, 74–93.5) and 93.5 mm Hg (interquartile range, 83–99), respectively. Conclusions: This case-series study showed feasibility of delineating real trends of the cerebral autoregulation plateau and direct visualization of the cerebral autoregulation curve after at least 24 hours of recording without manipulation of mean arterial blood pressure by external stimuli. The integration of multimodal monitoring at the bedside with cerebral oximetry provides a noninvasive method to delineate daily individual cerebral autoregulation curves. Abstract : Supplemental Digital Content is available in the text.